Estimating the supply of biomass from short-rotation coppice in England, given social, economic and environmental constraints to land availability. Issue 5 (September 2010) - Aylott, Matthew J; Casella, Eric; Farrall, Kate; Taylor, Gail
Background: Biomass has been identified as an important source of renewable energy. However, growing demand for dedicated energy crops could lead to conflicts with food production and ecosystem services. This study uses a geographic information systems-embedded modeling approach to assess the spatial supply of short-rotation coppice, taking into account social, economic and environmental constraints.Results: Results suggest that 7.5 million tons of biomass (from short-rotation coppice) is realistically available in England. Such production would require 0.8 million ha and could be grown almost entirely on poor quality marginal lands.Conclusion: We therefore conclude that short-rotation coppice energy crops have the potential to play an important role in meeting UK renewable energy targets without compromising environmental sustainability or food production.